Functional aspects of meningeal lymphatics in ageing and Alzheimer's disease. (9th August 2018) - Mesquita, Sandro; Louveau, Antoine; Vaccari, Andrea; Smirnov, Igor; Cornelison, R.; Kingsmore, Kathryn; Contarino, Christian; Onengut-Gumuscu, Suna; Farber, Emily; Raper, Daniel; Viar, Kenneth; Powell, Romie; et al.
Abstract Ageing is a major risk factor for many neurological pathologies, but its mechanisms remain unclear. Unlike other tissues, the parenchyma of the central nervous system (CNS) lacks lymphatic vasculature and waste products are removed partly through a paravascular route. (Re)discovery and characterization of meningeal lymphatic vessels has prompted an assessment of their role in waste clearance from the CNS. Here we show that meningeal lymphatic vessels drain macromolecules from the CNS (cerebrospinal and interstitial fluids) into the cervical lymph nodes in mice. Impairment of meningeal lymphatic function slows paravascular influx of macromolecules into the brain and efflux of macromolecules from the interstitial fluid, and induces cognitive impairment in mice. Treatment of aged mice with vascular endothelial growth factor C enhances meningeal lymphatic drainage of macromolecules from the cerebrospinal fluid, improving brain perfusion and learning and memory performance. Disruption of meningeal lymphatic vessels in transgenic mouse models of Alzheimer's disease promotes amyloid-β deposition in the meninges, which resembles human meningeal pathology, and aggravates parenchymal amyloid-β accumulation. Meningeal lymphatic dysfunction may be an aggravating factor in Alzheimer's disease pathology and in age-associated cognitive decline. Thus, augmentation of meningeal lymphatic function might be a promising therapeutic target for preventing or delaying age-associated neurological diseases. Meningeal lymphatic dysfunction promotes amyloid-β deposition in the meninges and worsens brain amyloid-β pathology, acting as an aggravating factor in Alzheimer's disease and in age-associated cognitive decline; improving meningeal lymphatic function could help to prevent or delay age-associated neurological diseases.